PENGARUH FINTECH PAYMENT, PERILAKU KONSUMTIF, DAN PENGENDALIAN DIRI TERHADAP PENGELOLAAN KEUANGAN PENGGEMAR K-POP - Herlina Herlina; Fransisca Carolina; Jeammy Nolen (Creative Research Management Journal, 2025)
South Korean culture's influx into Indonesia has had a significant impact on various aspects of people's lives. One of the most impacted areas is the music world, particularly the music genre known as Hallyu or the Korean wave, commonly referred to as K-Pop. K-Pop fans have specific needs and desires that must be met, but remain limited by their financial situation. Therefore, financial management is crucial for them. This study aims to analyze the influence of fintech payments, consumer behavior, and self-control on the financial management of K-Pop fans. The sampling method used was non-probability sampling with a purposive sampling approach. The total number of respondents was 486 people, with the criteria being K-Pop fans aged at least 15 years and having purchased merchandise, concert tickets, or other items related to K-Pop. In the data analysis process, the researcher used multiple linear regression with the help of SPSS. The results showed that fintech payments did not significantly influence financial management, while consumer behavior and self-control had a significant influence on the financial management of K-Pop fans. This finding provides an empirical contribution by confirming that K-Pop fans' financial management is more determined by psychological and behavioral factors, especially consumer behavior and self-control, than by the use of fintech payments, so that the implications emphasize the importance of financial education policies and programs that focus on controlling consumption and strengthening self-control rather than simply literacy in the use of digital payment technology.